Childhood Stunting, Wasting, and Obesity, as the Critical Global Health Issues: Forging Cross-Sectoral Solutions 2020
DOI: 10.26911/the7thicph.02.52
|View full text |Cite
|
Sign up to set email alerts
|

Breakfast and Hemoglobin Level among Female Junior High School Student In Surakarta, Central Java

Abstract: Background: Physical activity among school-age adolescents make them skipping the breakfast. Skipping breakfast can cause a loss of energy and nutrients needed for hemoglobin (Hb) synthesis. This study aimed to examine the effect of breakfast on anemia levels among female adolescent. Subjects and Method: A cross-sectional was conducted by involving 30 female adolescent aged 13-15. The study subjects were divided into 30 female adolescent had breakfast group and 30 female adolescent had no breakfast group. Bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…Eritrosit berperan dalam menyediakan O2 ke jaringan tubuh (Helms et al, 2018) Hemoglobin pada manusia memiliki nilai normal yaitu pada perempuan 12-15 g/dL dan laki -laki 13-17 g/dl (Gunadi, 2016) Kasus anemia terbanyak mayoritas berada di negara berkembang, sebanyak 124 negara berkembang diketahui terdapat kasus anemia. Data Riset Kesehatan Dasar pada tahun 2018, angka kejadian anemia pada remaja sebesar 32% dimana hal tersebut kontras dengan standar nasional kejadian anemia yaitu sebesar 20% (Elisa, 2023) Menurut data hasil Riskesdas tahun 2013 remaja putri mengalami anemia yaitu 37,1%, mengalami peningkatan menjadi 48,9% pada Riskesdas 2018, dengan proporsi anemia ada di kelompok umur 15-24 tahun dan 25-34 tahun (Kartika, 2020) Anemia merupakan permasalahan kesehatan yang sering terjadi pada remaja. Masa remaja adalah periode pertumbuhan paling cepat kedua setelah masa kanakkanak.…”
Section: Pendahuluanunclassified
“…Eritrosit berperan dalam menyediakan O2 ke jaringan tubuh (Helms et al, 2018) Hemoglobin pada manusia memiliki nilai normal yaitu pada perempuan 12-15 g/dL dan laki -laki 13-17 g/dl (Gunadi, 2016) Kasus anemia terbanyak mayoritas berada di negara berkembang, sebanyak 124 negara berkembang diketahui terdapat kasus anemia. Data Riset Kesehatan Dasar pada tahun 2018, angka kejadian anemia pada remaja sebesar 32% dimana hal tersebut kontras dengan standar nasional kejadian anemia yaitu sebesar 20% (Elisa, 2023) Menurut data hasil Riskesdas tahun 2013 remaja putri mengalami anemia yaitu 37,1%, mengalami peningkatan menjadi 48,9% pada Riskesdas 2018, dengan proporsi anemia ada di kelompok umur 15-24 tahun dan 25-34 tahun (Kartika, 2020) Anemia merupakan permasalahan kesehatan yang sering terjadi pada remaja. Masa remaja adalah periode pertumbuhan paling cepat kedua setelah masa kanakkanak.…”
Section: Pendahuluanunclassified
“…Regardless of the reason, this behavior has been associated with detrimental effects in adolescents, as breakfast skipping is a known risk factor for anemia (Abalkhail & Shawky, 2002; Ropitasari et al, 2020) and odds of anxiety, depression, and psychological distress (Zahedi et al, 2022). Moreover, breakfast skipping has been found to be associated with unhealthy lifestyles in adolescents, particularly with smoking (Kapantais et al, 2011) and poorer dietary quality (O'Neil et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review of 33 countries (of which 23 were high‐income nations) reported that 10–30% of adolescents skip breakfast, and is more common in girls (Keats et al, 2018; Monzani et al, 2019). This high prevalence is concerning as the nutritional consequences of missing breakfast have been described in several observational and some intervention studies and can have significant implications for the health and well‐being of adolescents in LMICs (Onyiriuka et al, 2013; Ropitasari et al, 2020; Zahedi et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation